Framework LTSA untuk Analisis dan Pengembangan Learning Management System Dalam Mendukung Peningkatan Proses Pembelajaran - Nur Aini; Sarjon Defit; S Sumijan (LPPM STIKOM Tunas Bangsa, 2024)
Learning Management System is a software for the need to manage learning activities such as searching for materials, reporting learning matters, providing materials for learning matters carried out online and connected to an internet connection. The benefits that can be obtained Form the use of e-learning are the existence of facilities for e-moderating where teachers can carry out learning activities without being constrained by distance, teachers and students can also use teaching materials via the internet, students can review learning materials online, if students require additional materials for learning so students can access the internet, changes in the role of students and teachers become more active and learning is relatively more efficient and effective. This research aims to apply the LTSA framework to the design of a Learning Management System. The method used in this research is the LTSA framework. This method explains that the LTSA framework consists of five architectural layers, each layer describes a system at a different level. The dataset processed in this research comes Form SMK N 1 Ranah Batahan. The dataset consists of students majoring in TKJ class XI in Indonesian, English, mathematics and vocational subjects. The results of research using the LTSA framework make learning data more structured in managing learning activities. This research can be a reference in developing a Learning Management System using other methods